Geriatric perioperative care. (January 2021) - Ibitoye, Sarah; Braude, Philip
Abstract: The number of older people undergoing surgery is increasing yearly. Older adults are more likely to present for emergency surgery than undergo an elective operation. Advanced age, frailty, multimorbidity, cognitive impairment, and urgency of surgery are all predictors of poor outcome, including functional and cognitive decline. A new field led by geriatric medicine has grown to manage the specific issues that older people face when preparing for, undergoing, or recovering from surgery. Perioperative comprehensive geriatric assessment (CGA) is a multidimensional process that can be used to identify risk, optimize health and support complex decision-making before surgery; and is associated with reduced postoperative morbidity and mortality. Estimation of perioperative mortality should be recorded and discussed for all older patients, especially those with frailty. Factors such as frailty, cognition, and the person's priorities for care, are key to understanding perioperative risk where outcomes such as functional and cognitive decline may be more concerning to the person than death. Geriatrician co-management of older people undergoing surgery is associated with improved outcomes in a range of surgical specialties, with the most robust evidence for hip fracture and emergency laparotomy, and increasing evidence for vascular surgery and major trauma.